Avaliação do selante de fibrina como arcabouço para células tronco em fígados cirróticos - Silvestre, Priscila Modesto [UNESP] (2015)
Introduction: Cirrhosis is the final stage of liver disease mainly caused by viral hepatitis, alcohol intake, and currently it can only be reversed by liver transplantation. In a new assessment of mortality of liver cirrhosis by design Global Burden of Disease (GBD) in the BMC Medicine, a variety of methods and data sources has led to an overall estimate of just over a million deaths in 2010, which was about 2% of all deaths. In recent years, research has intensified on biotech issues, favoring therapeutic discovery of stem cells to cirrhosis, which have generated great expectations in tissue regeneration of the liver and its application. However, a major problem faced was its low setting in cirrhotic liver, with spread to the whole body and without the expected effectiveness. The investigations have not yet found a way to effectively prevent stem cells spread to other organs reducing their effectiveness regeneration. AIM: Evaluate the fibrin glue derived from snake venom (SFDPS) as a scaffold for stem cells in cirrhotic livers. Methods: The model of experimental cirrhosis in rats was induced by Thioacetamide (C2H5NS), twice per week intraperitoneally (iv) at 200 mg / kg. The of blood collection was performed for biochemical analysis in B200 equipment. Isolation of stem cells was performed according Gasparotto et al. 2014. The markup for cytometry was performed on the second pass with markers RT1 AW2 FITC, CLASS RT1 PE, CD11b, CD44, CD90, CD34, CD105, CD73, CD45, ICAM. The biomarker of serine protease was performed with Alexa Fluor 488 Protein Labeling Kit (A30006v) kit. The surgery has been realized with inhalational anesthesia, the animals were separated into three groups where they received the treatment selected. Histology of 5μm sections were hematoxylin and eosin for staining (HE) and Picrosirius. Immunostaining was performed according to kit Click-it ® Imaging kits EdU. RESULTS: The development of cirrhosis was macroscopically ...